PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS)UNTUK MENINGKATKAN KEMAMPUAN MEMBEDAKAN FAKTA DAN OPINI PADA SISWA KELAS IV SD NEGERI 2 SETIA MULIA - Ana Mustopiah; Al-Amin (ADIBA : JOURNAL OF EDUCATION, 2026)
This study is motivated by the low ability of fourth-grade students at SD Negeri 2 Setia Mulia in distinguishing facts and opinions in Indonesian language learning. This condition is shown by the initial observation results indicating that most students have not reached the Minimum Mastery Criteria. Learning is still dominated by lecture methods, causing students to be less active and less involved in the process of text analysis. This study aims to improve students’ ability to distinguish facts and opinions through the implementation of the Think Pair Share (TPS) learning model. The research method used is Classroom Action Research with a qualitative approach supported by simple quantitative data. The research subjects were 25 fourth-grade students at SD Negeri 2 Setia Mulia. Data collection techniques included observation, tests, and documentation. The results showed an improvement in students’ abilities from Cycle I to Cycle II. In Cycle I, most students were still below the mastery criteria, while in Cycle II there was a significant improvement with most students achieving mastery learning. The Think Pair Share model proved to enhance students’ learning activity, confidence, and critical thinking skills in distinguishing facts and opinions. The conclusion of this study shows that the implementation of the Think Pair Share model is effective in improving students’ ability to distinguish facts and opinions. The recommendation of this study is that teachers can apply the TPS model as an active and interactive learning alternative to improve the quality of Indonesian language learning.